2015
DOI: 10.1109/jbhi.2015.2469540
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a Trunk Accelerometer System to the Characterization of Gait in Patients With Mild-to-Moderate Parkinson's Disease

Abstract: Gait quantified by a trunk accelerometer may provide clinically useful information for the screening and follow-up of PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Only one work (Salarian et al, 2009 ) was focused on turning; it recognized differences between early PwPD and HC with excellent sensitivity and reliability thanks to the automatic detection of all turns. The majority of the works compared the performances of a group composed of PwPD and a group of control subjects (Barth et al, 2013 ; Palmerini et al, 2013 ; Arora et al, 2014 ; Oung et al, 2015 ; Parisi et al, 2015 ), and showed that the second group had better results in terms of time of execution, speed (Horak et al, 2016 ), regularity, cadence, symmetry, stride length (Demonceau et al, 2015 ), amplitude, and slope (Weiss et al, 2011 ). Others implemented multi-class classification to distinguish among HC, PwPD without gait disturbance, and PwPD with gait disturbance (Tien et al, 2010 ) or compared the performance of HC, PwPD, and subjects with dementia (Yoneyama et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one work (Salarian et al, 2009 ) was focused on turning; it recognized differences between early PwPD and HC with excellent sensitivity and reliability thanks to the automatic detection of all turns. The majority of the works compared the performances of a group composed of PwPD and a group of control subjects (Barth et al, 2013 ; Palmerini et al, 2013 ; Arora et al, 2014 ; Oung et al, 2015 ; Parisi et al, 2015 ), and showed that the second group had better results in terms of time of execution, speed (Horak et al, 2016 ), regularity, cadence, symmetry, stride length (Demonceau et al, 2015 ), amplitude, and slope (Weiss et al, 2011 ). Others implemented multi-class classification to distinguish among HC, PwPD without gait disturbance, and PwPD with gait disturbance (Tien et al, 2010 ) or compared the performance of HC, PwPD, and subjects with dementia (Yoneyama et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In several studies, moderate patients (e.g., HY = 2/3, Palmerini et al, 2013 ; Yoneyama et al, 2013 ; Sejdić et al, 2016 ) were involved, so the difference in performance between PwPD and HC are easily identifiable. The recruitment of PwPD in the first stage of the disease (i.e., HY = 1) should be primarily investigated to demonstrate the accuracy and the objectivity of the technological solutions with respect to the traditional clinical evaluations (Demonceau et al, 2015 ), aiming to achieve early diagnosis of the pathology (Barth et al, 2011 ). Many gait analysis protocols have been developed to complete the medical exam of PD patients, but the optimal method remains under debate (Demonceau et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies of interest include [24,26,29], which are quite different compared to the other studies reviewed in this section, as they do not aim to extract standard gait metrics. However, they are worthy of attention since they aim to extract balance and symmetry-related upper-body features from the raw data of sensors placed on the trunk.…”
Section: Related Work On Gait Analysis With Imusmentioning
confidence: 99%
“…[32] reports the usage of accelerometers located at a patient's both wrists and the left ankle to monitor the Parkinson's disease. In [33], the same disease is monitored by using accelerometers installed at the trunk of a patient. For sports applications, [34] presents a motions tracking system based on inertial sensors placed at the hip, leg and foot.…”
Section: Selection Of Antenna Locations and Measurement Implementationmentioning
confidence: 99%